Evidence for a physiological role of pulmonary arterial baroreceptors in sympathetic neural activation in healthy humans. (14th February 2020) - Simpson, Lydia L.; Meah, Victoria L.; Steele, Andrew; Thapamagar, Suman; Gasho, Christopher; Anholm, James D.; Drane, Aimee L.; Dawkins, Tony G.; Busch, Stephen A.; Oliver, Samuel J.; Lawley, Justin S.; Tymko, Michael M.; et al.
Abstract : Key points: In an anaesthetised animal model, independent stimulation of baroreceptors in the pulmonary artery elicits reflex sympathoexcitation. In humans, pulmonary arterial pressure is positively related to basal muscle sympathetic nerve activity (MSNA) under conditions where elevated pulmonary pressure is evident (e.g. high altitude); however, a causal link is not established. Using a novel experimental approach, we demonstrate that reducing pulmonary arterial pressure lowers basal MSNA in healthy humans. This response is distinct from the negative feedback reflex mediated by aortic and carotid sinus baroreceptors when systemic arterial pressure is lowered. Afferent input from pulmonary arterial baroreceptors may contribute to sympathetic neural activation in healthy lowland natives exposed to high altitude. Abstract: In animal models, distension of baroreceptors located in the pulmonary artery induces a reflex increase in sympathetic outflow; however, this has not been examined in humans. Therefore, we investigated whether reductions in pulmonary arterial pressure influenced sympathetic outflow and baroreflex control of muscle sympathetic nerve activity (MSNA). Healthy lowlanders ( n = 13; 5 females) were studied 4–8 days following arrival at high altitude (4383 m; Cerro de Pasco, Peru), a setting that increases both pulmonary arterial pressure and sympathetic outflow. MSNA (microneurography) and blood pressure (BP; photoplethysmography) were measured continuously during ambient air breathing (Amb) and a 6 min inhalation of the vasodilator nitric oxide (iNO; 40 ppm in 21% O2 ), to selectively lower pulmonary arterial pressure. A modified Oxford test was performed under both conditions. Pulmonary artery systolic pressure (PASP) was determined using Doppler echocardiography. iNO reduced PASP (24 ± 3 vs . 32 ± 5 mmHg; P < 0.001) compared to Amb, with a similar reduction in MSNA total activity (1369 ± 576 to 994 ± 474 a.u min −1 ; P = 0.01). iNO also reduced the MSNA operating point (burst incidence; 39 ± 16 to 33 ± 17 bursts·100 Hb −1 ; P = 0.01) and diastolic operating pressure (82 ± 8 to 80 ± 8 mmHg; P < 0.001) compared to Amb, without changing heart rate ( P = 0.6) or vascular–sympathetic baroreflex gain ( P = 0.85). In conclusion, unloading of pulmonary arterial baroreceptors reduced basal sympathetic outflow to the skeletal muscle vasculature and reset vascular–sympathetic baroreflex control of MSNA downward and leftward in healthy humans at high altitude. These data suggest the existence of a lesser‐known reflex input involved in sympathetic activation in humans. Key points: In an anaesthetised animal model, independent stimulation of baroreceptors in the pulmonary artery elicits reflex sympathoexcitation. In humans, pulmonary arterial pressure is positively related to basal muscle sympathetic nerve activity (MSNA) under conditions where elevated pulmonary pressure is evident (e.g. high altitude); however, a causal link is not established. Using a novel experimental approach, we demonstrate that reducing pulmonary arterial pressure lowers basal MSNA in healthy humans. This response is distinct from the negative feedback reflex mediated by aortic and carotid sinus baroreceptors when systemic arterial pressure is lowered. Afferent input from pulmonary arterial baroreceptors may contribute to sympathetic neural activation in healthy lowland natives exposed to high altitude.